Leaf Extract Microencapsulation of Stevia rebaudiana Bert Using Inulin-Chitosan as Anti-Diabetes Diet - Mutmainah Mutmainah; Yohanes Martono; Ika Puspitaningrum; Lia Kusmita (Journal of Tropical Pharmacy and Chemistry, 2021)
Diabetes mellitus is a collection of symptoms that arise in someone who has increased blood glucose levels. The Stevia plant (Stevia rebaudiana Bert) contains a compound of diterpene glycosides as steviosida and rebaudiosida A. Purified extract of steviosida and rebaudiosida A is widely used as a sweetener for low calorie food and beverage products or as a sugar substitute for diabetics and has the effect of lowering blood sugar levels. This study aims to determine the antidiabetic effect of microencapsulated preparations of Stevia leaf extract (Stevia rebaudiana) with a combination of inulin chitosan encapsulation. Antidiabetic mellitus test was carried out in vivo using test animals of male white rats of Wistar strain. The inducing compound that can cause the condition of diabetes mellitus test animals is Aloxan with a dose of 150 mg / kg Body weight of rats. given intraperitoneally for one day, then the mice were allowed to stand for 3 days to reach a state of diabetes mellitus. Blood glucose levels of test animals were measured on days 1 (initial), 5 (induction) and 12 (treatment) to determine the initial blood glucose levels, after induction of alloxan and after administration of test compounds both CMC Na 0.5% , glibenclamide, and preparations microencapsulation of Stevia leaf extract at a dose of 100; 300; and 700 mg / kg body weight. The results were obtained after 7 days of treatment, it was seen that blood glucose levels in the CMC group remained high, while the Glibenclamid administration group, and the three dosages of microencapsulation preparations of Stevia leaf extract could reduce blood glucose levels. This can be seen from the statistical test that there is a significant difference (p